A dynamic analysis of household decision making in urban Colombia, 1976-1998: changes in household structure, human capital and its returns, and female labor force participation (1999)
The objective of this research paper is to examine the changes and dynamics of household structure, human capital and the returns to education, labor earnings, women labor force participation and investment in human capital. The approach used in the analysis is the so-called "cohort technique", which consists in following across time men and women born in the same year or year spell. The main sources of information for this work are the quarterly Household Surveys beginning in 1976. With such information a database of more than 6.0 millions observations (workers, parents, children, etc) was constructed. The research results show that the number of children of the younger parents has drastically decreased. This process has come together with a significant increase in women's labor force participation and higher women's school attainment. The study also points out that the school attainment of the younger generation of women is higher than men's and that the income gap between men and women of the new generation, after controlling by education, is lower than such gap in the old generations. Finally, the study indicates that the human capital accumulation has been very unequal for the different income groups. The children of low educated parents achieve low levels of education both in the old and new generations. Thus, the escaping from the poverty trap is as difficult today as in the past. The education opportunities are concentrated in the middle and high-income groups.